The Rulal board game: Enabling policy practitioners and students to experience how natural resource management decisions are shaped by power relations and power dynamics - CGIAR Research Program on Policies, Institutions, and Markets (2019)
Rulal was presented at various workshops and conferences, included in teaching materials at universities (Wageningen University and Research, Ubon Ratchathani University) and used as training material for civil society groups in Laos.